Traffic information and control - Li, Ruimin, 1979-; He, Zhengbing (Of Beijing gong ye da xue) (The Institution of Engineering and Technology, 2020)
"Written by an international team of researchers, this book focuses on traffic information processing and signal control using emerging types of traffic data. It conveys advanced methods to estimate and predict traffic flows at different levels, including macroscopic, mesoscopic and microscopic. The aim of these predictions is to optimize traffic signal control for intersections and to mitigate ever-growing traffic congestion. A valuable resource for researchers and engineers working in the field of traffic information and control, and intelligent transport systems, Traffic Information and Control offers an overview of recent research and practical approaches to optimising traffic signal control."-- Provided by publisher.
Keywords: Intelligent transportation systems.; Transportation -- Information services.; Traffic engineering -- Data processing.; Traffic flow.; Traffic signs and signals.; Machine learning.; elektronické knihy; electronic books